Difficulties in diagnostics of atypical hemolytic uremic syndrome in the intensive care unit - N. L. Kozlovskаya; G. M. Gаlstyan; V. N. Stepаnyuk (Вестник анестезиологии и реаниматологии, 2019)
Atypical hemolytic uremic syndrome (aHUS) is an orphan disease, representing one of thrombotic microangiopathies, the natural course of which leads to an unfavorable outcome often accompanied by multiple organ failure in the onset of the disease. Anesthesiologists and emergency physicians play an important role in the multi-disciplinary team of specialists managing such patients. However, this disease is rare and its symptoms are similar to the ones of some other disorders including sepsis and disseminated intravascular coagulation syndrome, thus often aHUS is diagnosed late and specific treatment is not started in time. This article aims to present main notions related to thrombotic microangiopathies and discuss topical issues of differential diagnostics of aHUS in the intensive care units giving two clinical cases as an example.